Urejanje medsebojnih razmerij etažnih lastnikov de lege ferenda - Juhart, Miha (Podjetje in delo, 2017)
The legal relationship of strata-title ownership consists of two elements: property and community among the apartments owner. In the current law, this relationship is regulated by the Property Code, the Housing Act and the Act on the Acquisition of the Strata Title of a Part of a Building. The latter is of a transitory nature, as it refers to the reconciliation of unsettled relations from the past. The legal rules in the Property Code and the Housing Act duplicate or sometimes come into substantive conflicts. The author primarily draws attention to the problem of a compulsory contract on mutual relationships among apartment owners. The author advocates a change of the concept, which should define this contract as dispositive. However, the statutory arrangement should regulate mutual relationships and allow special provisions and rules based on the expressed will of the owners.
Keywords: contract on mutual relationships among apartment owners; etažna lastnina; Housing Act; pogodba o medsebojnih razmerjih; Property Code; stanovanjski zakon; strata-title ownership; stvarnopravni zakonik